Firewood cable extraction in the southern Mediterranean area of Italy. Issue 1 (2nd January 2016) - Proto, A.R.; Zimbalatti, G.
Abstract : This research assesses the efficiency and the costs of different cable cranes used in harvesting, in the forests of the southern Mediterranean area of Italy. During the study process a total of 100 cycle times were recorded in order to obtain the average performance. The cable cranes were tested in six different sites. Machine costs make up an essential part of timber harvesting costs; it is necessary to analyze these costs in order to decide which methods or machine types to use. Costs have been calculated using a standard hourly method. The present investigation showed that the three cable cranes extracted inferior volumes of timber compared to their load potential; in fact, the average extracted volume was inferior compared to the load capacity of the carriage. Nevertheless, from the comparison between cost per m 3 and the market price of firewood, sufficient margins of value for the producer emerged. The level of productivity analyzed on these different sites showed that unproductive time influenced the extraction costs of wood. In fact, when the three cable cranes were productive the extraction cost of 1 m 3 of firewood varied from €20.89 to €27.84.